Long-Term Athletic Development, Part 2: Barriers to Success and Potential Solutions. Issue 5 (May 2015) - Lloyd, Rhodri S.; Oliver, Jon L.; Faigenbaum, Avery D.; Howard, Rick; De Ste Croix, Mark B. A.; Williams, Craig A.; Best, Thomas M.; Alvar, Brent A.; Micheli, Lyle J.; Thomas, D. Phillip; Hatfield, Disa L.; Cronin, John B.; et al.
Abstract : Abstract: Lloyd, RS, Oliver, JL, Faigenbaum, AD, Howard, R, De Ste Croix, MBA, Williams, CA, Best, TM, Alvar, BA, Micheli, LJ, Thomas, DP, Hatfield, DL, Cronin, JB, and Myer, GD. Long-term athletic development: Part 2: Barriers to success and potential solutions. J Strength Cond Res 29(5): 1451–1464, 2015—The first installment of this two-part commentary reviewed existing models of long-term athletic development. However, irrespective of the model that is adopted by practitioners, existing structures within competitive youth sports in addition to the prevalence of physical inactivity in a growing number of modern-day youth may serve as potential barriers to the success of any developmental pathway. The second part of this commentary will initially highlight common issues that are likely to impede the success of long-term athletic development programs and then propose solutions that will address the negative impact of such issues.